Emergence of infection with Aphanomyces invadans in fish in some main aquatic ecosystems in Zimbabwe: A threat to national fisheries production. Issue 6 (7th June 2018) - Sibanda, Sitokozile; Pfukenyi, Davies M.; Barson, Maxwell; Hang'ombe, Bernard; Matope, Gift
Abstract: The first outbreak on the African continent of infection with Aphanomyces invadans (the causative agent of epizootic ulcerative syndrome) in fish was confirmed in the Chobe‐Zambezi rivers in 2007. The emergence of massive outbreaks of infection with A. invadans in multiple fish species exposed serious aquatic biosecurity challenges in the Southern African region. This study investigated the incursion of infection with A. invadans in fish from the main aquatic ecosystems of Zimbabwe from 2012 to 2015 using data obtained from the Department of Livestock and Veterinary Services, Zimbabwe. In some outbreaks, fish samples were collected and tested at the University of Zambia, for confirmation by histopathology and species‐specific PCR. The infection was first confirmed at Darwendale water impoundment (Mashonaland West Province) in 2012, followed by Matabeleland South Province at Mtshabezi water impoundment and Nkankezi River (both 2013). An apparent southward spread continued in 2014, with virgin outbreaks at Ntalale water impoundment (Matabeleland South Province) and Mwenezi River in Midlands Province. In 2015, inland incursion was confirmed at Dutchman's Pool in Midlands Province and further north‐west at the Sanyati River Basin in Lake Kariba (Mashonaland West Province). In all outbreaks, infection with A. invadans was confirmed in seven fish species, namely the African sharptooth catfish ( Clarias gariepinus, Burchell, 1822), blunt‐toothed African catfish ( Clarias ngamensis Castelnau, 1861), yellow belly bream ( Serranochromis robustus Gunther, 1864), straight fin barb ( Enteromius paludinosus Peters, 1852), dashtail barb ( Enteromius poechii Steindachner, 1911), large‐mouth bass ( Micropterus salmoides Lac′epe′de, 1802) and the three‐spot tilapia ( Oreochromis andersonii Castelnau, 1861). Cases were most common in the African sharptooth catfish, with mortalities more pronounced in young fish of all species. The results suggested a gradual emergence of an intractable infection with A. invadans in fish in the main aquatic ecosystems of Zimbabwe, which may have negative impact on biodiversity conservation and aquaculture.